Nature as Psychological Mirror: An Ecocritical Reading of Laxmi Prasad Devkota’s The Lunatic - Ghimire, Kusum (Mindscape: A Journal of English & Cultural Studies, 2025)
In nature, where every rustling leaf and soft breeze seem to echo our emotions, we can see how closely our lives are connected to the world around us. This paper examines the ecocritical dimensions of Laxmi Prasad Devkota’s poem The Lunatic, focusing on the representation of nature as both a psychological mirror and a symbolic force. Through close reading and engagement with ecocritical frameworks, particularly those proposed by Cheryll Glotfelty and Lawrence Buell, the study analyzes how natural imagery reflects and amplifies the speaker’s emotional intensity, ethical concerns, and existential reflections. Devkota transforms nature from a passive backdrop into an active participant, where stones, rivers, and celestial phenomena articulate human consciousness, moral inquiry, and resistance to societal norms. The analysis demonstrates how The Lunatic critiques anthropocentrism and underscores the interconnectedness of human identity and the environment. By foregrounding nature’s symbolic and transformative roles, this study positions Devkota as an early ecological thinker in South Asian literature, contributing to the discourse on literature, environment, and human consciousness.